RELATIONSHIPS BETWEERELATIONSHIPS BETWEE RELATIONSHIPS BETWEE RELATIONSHIPS BETWEE RELATIONSHIPS BETWEERELATIONSHIPS BETWEE RELATIONSHIPS BETWEERELATIONSHIPS BETWEERELATIONSHIPS BETWEE RELATIONSHIPS BETWEERELATIONSHIPS BETWEERELATIONSHIPS BETWEEN ULTRASON - Sri Rachma Aprilita Bugiwati (Bionatura, 2009)
This experiment was done at 292 head of Japanese black bull at Kagoshima and Miyazaki Prefectural Experimental Stations Japan to find out the relationship between ultrasonic estimates of carcass traits and body measurements as one of criteria to select Japanese black bull. The carcass traits of 20 months of age were predicted using the ultrasonic machine. The body dimensions were measured at the end of performance test (12 months of age) and 16 months of age. The ultrasonic evaluation techniques were used to estimate Musculus Longissimus thoracis area between 6–7th and 12-13th ribs (MLTA6-7 and MLTA12- 13), Subcutaneous Fat Thickness (SFT), Intermuscular Fat Thickness (IMFT), Rib Thickness (RT) and Marbling Score (MS). Body measurements were taken on body weight (BW), withers height (WH), hip height (HH), body length (BL), chest girth (CG), chest depth (CD), chest width (CW), rump length (RL), hip width (HW), thurl width (TW) and pin bone width (PBW). Chest girth, chest width and chest depth at 12 and 16 months of age were showed the highest significant and positive correlations among the other body dimensions with ultrasonic estimated of carcass traits at 20 months of age. The ratio of contribution to predict MLTA6-7, MLTA12-13 and SFT at 20 months of age using the body dimensions at 12 months of age were higher than those of 16 months of age.Keywords: Keywords: carcass traits, body dimension, ultrasonic estimate, performance test, japanese black bull, correlation